Η συστημική θεωρία ως πλαίσιο για την αντιμετώπιση της προβληματικής συμπεριφοράς του παιδιού στο σχολείο - Γαλανάκη, Ε. (Παιδαγωγική Επιθεώρηση, 2000)
In this article we describe aspects of systems theory which are useful for the educator, the school psychologist, and the career counselor when coping with problem situations in school. Namely, we present the main systemic principles, such as circular causality, nonadditivity, equifinality, multifinality, morph stasis, morphogenesis, and the concept of rules. Next, we discuss in systemic terms the school-family contact when children's problem behavior occurs. Finally, we describe and question common dysfunctional views which deter us from adopting the systemic perspective and bring to an impasse our efforts to deal with problem situations in school.